Gentamicin induced acute hypereosinophilia - Manappallil, Robin George; Sabir, Mele Chelakkoth (Asian Journal of Medical Sciences, 2019)
Gentamicin, an aminoglycoside, has been used for the treatment of severe infections by both Gram positive and negative organisms. Nephrotoxicity and ototoxicity are the common adverse effects. The patient being described had urinary tract infection for which he received gentamicin, and developed hypereosinophilia. To the best of our knowledge, this is an unreported event.